Stage of Pricking of Pine Seedlings for Raising Planting Stock - Ghosh, R. C.; Singh, Bakhshish; Sharma, K. K. (Indian Forester, 1980)
An experiment to find out the stage at which the pine seedlings should be pricked out from the germination boxes to the polythene bags for raising the nursery stock of Pinus caribaea, P. patula and P. elliottii, was conducted in the research nursery of the Forest Research Institute, Dehra Dun (India) during 1976-77. Five treatments comprising of direct sowing in polythene bags (T1 ), pricking of seedlings into polythene bags immediately after start of germination (T2), pricking after the seed coat falls from the cotyledons (T3), pricking after the formation of terminal bud (T4) and pricking when the terminal bud opens and starts growing (T5 ), were tried in a randomized block design with five replications and 20 plants per plot. The results of the study show that the seedlings pricked after fall of seed coat gave significantly better height and diameter growth than the seedlings pricked at the other stages, there being no significant difference in between the seedlings pricked just after germination (T2) and those pricked after fall of seed coat (T3) for diameter growth in case of P.patula and P. elliottii and height growth in case of P. elliotii. The different stages of pricking had no significant effect on survival of the seedlings.Based on the overall performance of the seedlings, it is recommended that the young pine seedlings should be pricked from germination boxes into polythene bags just after the seed coat fall from the cotyledons, after germination.